Peran Intensitas dan Interaktivitas Penggunaan Media Sosial (Instagram dan Website Linktree) dalam Meningkatkan Tingkat Hunian Kamar (Occupancy) di Cambridge Hotel Medan - Christin Witasari Sinurat; Widya Octovia Rini Simanjuntak (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the role of intensity (frequency, duration, attention, appreciation) and interactivity (two-way communication and responsiveness: user-to-system, user-to-user, and user-to-document) in the use of Instagram and the Linktree platform to increase room occupancy at Cambridge Hotel Medan. A descriptive-exploratory qualitative approach was employed through in-depth interviews with 11 informants, including hotel management and guests, as well as digital content observation. The findings indicate that the intensity and interactivity of Instagram and Linktree managed by the hotel are responsive, adaptive, and personalized, particularly through Direct Messages (DM) and comment features. However, user-to-user interaction remains limited, reducing the potential for building a brand community based on User-Generated Content (UGC), such as reposting user content. The hotel’s social media intensity is consistently and systematically implemented, influencing audience intention to make room reservations. Since 2023, Linktree has been replaced by bit.ly as part of a strategic transition toward better integration with the hotel’s web-based system. This shift enhances efficiency in conversion processes and reflects the organization’s adaptability to a more integrated digital experience. Although Instagram DM supports responsive and personal communication, it has not yet optimally fostered mutual discourse or digital community engagement.